Implementation assessment of the national program for the prevention and control of cerebro-vascular diseases in Cienfuegos. Period 2000-2004. - Rubén Bembibre Taboada; Miguel Angel Buergo Zuaznábar; Julio Cortizo Hernández; Niurka Galende Hernández; Roberto Travieso Peña; Roxilena Manso Martín; Marcos D. Iraola Ferrer (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
Fundament: The cerebrovascular deseases are the third cause of death and the leading cause of disability in Cuba. Due to the seriousness of this situation it was created the National Program for the Prevention and Control of Cerebrovascular Deseases. Objective: to evaluate the main achievements in the execution of this program, specifically in the province of Cienfuegos. Methods: the prospective and descriptive study of a series of cases that engulfed all the patients with cerebrovascular deseases in the period of January the 1st,2000, to December 31st,2004 (n=3477). Data were obtained from the monthly and annually reports of the provincial comission; for the analysis of the deceased we counted on the reports of the Provincial Government of Health and of the State Commettee of Statistics. Results: we found a morbility rate of 192,26 per 100 000 inhabitants. The mortality rates decreased in 11,26 (from 82,51 to 71,25 per 100 000 inhabitants). The global lethality decreased in 13,74 (from 26,61 to 12,87 per 100 000 inhabitants): in infarcts, from 24,27 to 6,64; and in subarachnoid hemorrhage, from 39,21 to 24. An increment of favorable evolution in patients with brain attack and subarachnoid hemorrhage was notified, it did not happened with intracerebral hemorrhage. The evident outstanding results in the diminishing of progressive mortality and lethality during this five years support the correct decision of creating such a Program.